INDIA'S INTRA-INDUSTRY TRADE UNDER ECONOMIC LIBERALIZATION: TRENDS AND COUNTRY SPECIFIC FACTORS - Veeramani C (Centre for Development Studies-WP313, 2001)
This paper focuses on two aspects of India's intra-industry trade (IIT) in manufactured commodities under economic liberalization. First, it examines the changes in the intensity of multilateral IIT as between 1987-88, 1994-95 and 1998-99 to understand the impact of trade liberalisation on IIT. Second, within the theoretical framework of vertical IIT, it analyzes the influence of various country specific factors on the intensity and the probability of IIT in India's bilateral trade with hermajor trading partners. The findings confirmed the hypothesis that trade liberalization biases trade expansion towards IIT. In most of the industries, the increased levels of IIT are export-led, that is, caused by a faster growth of exports than of imports. The econometric exercise showed that, certain country specific factors which are found to be crucial in theory, are pertinent in determining the country pattern of India's IIT.